VARIABILITY OF CHLOROPHYLL-a CONCENTRATION OF THE NORTHERN SUMBAWA WATERS BASED ON Sea WiFS SATELLITE DATA - Bisman Nababan; Diki Zulkarnaen; Jonson Lumban Gaol (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2009)
Variability of chlorophyll-a concentrations of the northern Sumbawa waters was investigated based on SeaWiFS satellite data for the period of January 1998-December 2007. Chlorophyll-aconcentration was estimated employing OC4v4 algorithm. Chlorophyll-a concentrations of,SeaWiFS satellite data were obtained from the Goddard Space Flight Center, NASA archieve data. In general, fluctuations of chlorophyll-a concentration of the northern Sumbawa waters had three patterns i.e., the maximum with a range of 0,21-0,74 mg/m3 occurred during the West Season (November-February), the minimum with a range of 0.12-0.15 mg/m3 occurred during Transition Season I (March-April), and relatively high (second peak) with a range of 0.21-0.36 mg/m3 occurred during the mid-East Season until the beginning of Transition Season II (July-September).High chlorophyll-a concentration occurred during the West Season was closely related to the high rainfall, the possibility of vertical water mass mixing,and upwelling process in the northern coastal waters of Sumbawa. Meanwhile, the relatively high (second peak) of chlorophyll-aconcentration occurred in July-September was caused by the movement of water masses from the South of Makassar Strait containing relatively high chlorophyll-a concentrations and relatively low temperatures since upwelling processes occurred at this location in the same period. Keywords:Chlorophyll-a,northern Sumbawa waters, SeaWiFS, OC4v4, upwelling